Production Analysis and Management of Tuna (Thunnus spp.) in Maluku Province, Indonesia - Sessarea Husaini; Resty Puja Astriana; Friska Adilla; Rifki Nur Saputra; Jeprianto; Sudirman Adibrata; Robet Perangin-angin; Hasan Eldin Adimu (Yayasan Serumpun Karang Konservasi, 2025)
This study discusses the management of tuna (Thunnus spp.) fisheries in the Indonesia Fisheries Management Area (IFMA) 714, with a focus on the waters of Maluku Province during the 2020–2024 period. The study aimed to analyze the management of yellowfin tuna (Thunnus sp.) fisheries in the waters of Maluku Province within IFMA714. A quantitative descriptive method was employed using secondary data obtained from the Statistics Data Portal of the Ministry of Marine Affairs and Fisheries (MMAF). The analyzed data included tuna production, the number of fishing vessels, and dominant fishing gear types. The results showed that tuna production fluctuated throughout the observation period, increasing in 2021, declining in 2022 and 2023, and then increasing significantly again in 2024. These fluctuations were influenced by oceanographic conditions, climate change, weather conditions, fishing intensity, operational costs, and market demand for tuna commodities. The number of fishing vessels also changed from year to year, reflecting the level of tuna resource utilization in the Maluku region. In addition, the dominant fishing gear shifted from trolling lines to handlines in 2024, indicating a transition toward more selective and environmentally friendly fishing practices. The findings suggest that sustainable tuna fisheries management through the control of fishing intensity, the use of environmentally friendly fishing gear, strengthened monitoring, and data-based management is essential to maintain tuna resource sustainability while supporting the long-term economic viability of fishing communities in Maluku Province.